2017
DOI: 10.1002/jsfa.8156
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory‐scale milling of whole‐durum flour quality: effect of mill configuration and seed conditioning

Abstract: An ultracentrifugal mill configured with a rotor speed of 12 000 rpm, screen aperture of 250 µm, and seed conditioning moisture of 90 g kg resulted in a fine whole-wheat flour where 82% of particles were <150 µm, starch damage was 59 g kg , and flour temperature was below 35 °C. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…An ultracentrifugal mill with a milling capacity of 2–4 kg would be suitable for a single‐pass milling system for laboratory‐scale production of WWF and subsequent WW pasta. Deng and Manthey (2016) and Khalid (2016) determined optimal mill configurations for an ultracentrifugal mill to direct grind wheat into coarse or fine WWF and to regrind bran/germ/shorts removed by roller milling into coarse and fine bran flours. The ultracentrifugal mill grinds wheat grain into small particles by impact with a rotor blade and by shear between the rotor blade and screen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An ultracentrifugal mill with a milling capacity of 2–4 kg would be suitable for a single‐pass milling system for laboratory‐scale production of WWF and subsequent WW pasta. Deng and Manthey (2016) and Khalid (2016) determined optimal mill configurations for an ultracentrifugal mill to direct grind wheat into coarse or fine WWF and to regrind bran/germ/shorts removed by roller milling into coarse and fine bran flours. The ultracentrifugal mill grinds wheat grain into small particles by impact with a rotor blade and by shear between the rotor blade and screen.…”
mentioning
confidence: 99%
“…Research studies have shown that different milling systems and configurations produce WWF with widely different particle sizes and functionalities (Inamdar et al 2015; Liu et al 2015; Deng and Manthey 2016). Inamdar et al (2015) found that starch damage was lowest and rheological properties were better for WWF made by roller milling, a multipass system, than by milling with a hammer mill, disk mill, or pin mill, single pass‐systems.…”
mentioning
confidence: 99%
“…For the powder resulting from dry and semi-dry/wet grindings, the increase of initial moisture content increased the average particle size and the large particle fraction [8][9][10]27,32,35,36,42,44,45]. When the moisture content is low, the food material is brittle, and breakdown by force is applied.…”
Section: Particle Shape and Size Distributionmentioning
confidence: 99%
“…The initial moisture content influenced such grinding properties as average particle size, particle size distribution, grinding energy, product yield, grinding loss, etc. In most grinding results, materials with high moisture content had larger average particle sizes and higher grinding energy consumption than the powder produced by low moisture materials, because foods with high moisture content became difficult to grind since water acts as a plasticizer [9,10,14,35,36,43,44]. The water made the materials soft, so that they resisted the size reduction during the grinding process.…”
Section: The Influence Of Moisture Content On the Grinding Characterimentioning
confidence: 99%
See 1 more Smart Citation